Fabrication Of Rhizophora Spp. Head Phantom For External Beam Radiotherapy Applications - Zuber, Siti Hajar (2022)
The aim of this study was to fabricate a head phantom made from soy-lignin Rhizophora spp. for dosimetric applications in external beam radiotherapy (EBRT) of the brain. Three different particle sizes (0–103 μm, 104–210 μm, 211–500 μm) and different percentages of adhesives (0, 6 and 12%) were studied for the production of the particleboards at target density of 1.0 g·cm-3. The particleboards were also evaluated with three different coating mixtures for surface smoothness. Characterisation of the particleboards were carried out to determine the physical, chemical and mechanical properties of the fabricated particleboard. This includes thermogravimetric analysis (TGA), Fourier transform infrared (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), carbon hydrogen nitrogen (CHN), internal bonding, water absorption, thickness swelling, crystallinity and elemental composition analyses. The particleboards were also investigated in terms of computed tomography (CT) number, attenuation, Compton scattering and percentage depth dose (PDD). Next, a head phantom was constructed using the best particleboard formulation. For brain irradiation, three-dimensional conformal radiation therapy (3D-CRT) technique was used, with a prescribed dose of 30 Gy in 10 fractions.